Governing the Good State Shareholder: The Case of the OECD Guidelines on Corporate Governance of State-Owned Enterprises - Mikko Rajavuori (Netherlands, 2022)
The newly revised Guidelines on Corporate Governance of State-Owned Enterprises (2015) by the OECD are fast emerging as a new regulatory paradigm for the administration of State-owned enterprises and the organization of the State ownership function. This article analyses the Guidelines’ policy prescriptions, governance strategies, and integration into global governance. Noting that the instrument operates by governing the shareholder’s internal make-up, decision-making and objective setting, the article argues that the Guidelines amount to a robust model for an ideal State shareholder—the Good State Shareholder. Efficient, engaged, and accountable, the Good State Shareholder emerges as a critical actor in the contemporary global economy, where States continue to amass and command immense shareholder power. However, when juxtaposed with the recent attempts by the UN to adopt State ownership as an instrument of human rights governance, the fault lines of the Good State Shareholder model, as well as the emerging techniques of shareholder governance, are exposed.